Study of risk taking behaviors and practices long route drivers in Dharan Municipality of Eastern Nepal - Uprety, Samyog; Ghimire, A; Poudel, M; Baral, DD (Health Renaissance, 2017)
Background: Due to its perception as a disease of development, road traffic accident and related injuries tend to be under recognized as a major health problem in developing countries. However, majority of the world's fatalities on the roads occur in low income and middle income countries. Since the main cause of road traffic accident is attributed to human risky behaviors, it is important to identify significant factors for risky behaviors of drivers. Objective: To know the risk taking behavior among drivers and practices of driving. Methods: This population based cross-sectional study. The study was conducted in Dharan, a township in Eastern Nepal. The study population includes of all long route drivers who are registered in membership of vehicle organization. Modified semi structured questionnaire was used for data collection. SPSS version 11.5 computer software was used for data entry and analysis. Results: Majority of study population belong to 25-29 years group. Majority of the drivers had valid license (98%) and about 68.9% drivers didn’t had any formal driving training school prior starting driving vehicle Most of them drive in high speed at highways but majority ignored that they take alcohol while driving. with growing age, years of driving had correlation of accidents among drivers population Conclusion: Study population comprises of youth drivers and most they had valid lenience. With the growing age drivers are neglecting traffic rules and sings and young driver are driving vehicles with overconfidently Health Renaissance 2015;13 (3): 1-6